Personalized treatment of brain metastases: Evolving survival prediction models may benefit from evaluation of serum tumor markers (narrative review) - Nieder, Carsten; Andratschke, Nicolaus H.; Grosu, Anca L. (Frontiers in Oncology, 2022)
Treatment of a limited number of brain metastases (oligometastases) might include complex and sometimes invasive approaches, e.g. neurosurgical resection followed by post-operative stereotactic radiotherapy, and thus, correct identification of patients who are appropriate candidates is crucial. Both, staging procedures that visualize the true number of metastastic lesions and prognostic assessments that identify patients with limited survival, who should be managed with less complex, palliative approaches, are necessary before proceeding with local treatment that aims at eradication of all oligometastases. Some of the prognostic models, e.g. the LabBM score, include blood biomarkers believed to represent surrogate markers of disease extent. In a recent study, patients with oligometastases and a LabBM score of 0 (no abnormal biomarkers) had an actuarial 5-year survival rate of 27% after neurosurgical resection and 39% after stereotactic radiotherapy. Other studies have tied serum tumor markers such as carcinoembryonic antigen (CEA) to survival outcomes. Even if head-to-head comparisons and large-scale definitive analyses are lacking, the available data suggest that attempts to integrate tumor marker levels in blood biomarker-based survival prediction models are warranted.